Prediction of Song Popularity Based on BILLBOARD Chart Using The NAÏVE BAYES Algorithm - Farid Sanitas Bachtiar (Universitas PGRI Semarang, 2018)
To find out if a song is popular or not, song lovers usually specify certain criteria such as artist, record label, genre, collaboration or featuring, and soundtrack. Another way that can be done is to seek information from the internet. One of the sites that can be a solution for the song lovers to know the popularity of a song that is Billboard. Billboard has been a trusted source for song popularity ratings over the last 60 years, and most record labels refer to the ratings given by Billboard. But the song lovers can not make billboards as a reference to determine the popularity of a song. Therefore, in this study the method of Naïve Bayes Classifier will be used to predict the popularity of a song based on the Billboard charts so as to help the song lover to determine the popularity of a song.